Original paperCan we improve the dose distribution for single or multi-lumen breast balloons used for Accelerated Partial Breast Irradiation? - Skowronek, Janusz; Bielęda, Grzegorz; Łaski, Piotr; Kycler, Witold (Journal of Contemporary Brachytherapy, 2013)
Purpose : The aim of the study was to verify dose distribution parameters for multi-lumen, and artificially created single-lumen balloon applicator used for the same patient with two optimization algorithms: inverse planning simulated annealing (IPSA) and dose point optimization with distance option. Material and methods : Group of 24 patients with multi-lumen balloon applied were investigated. Each patient received 10 fractions of 3.4 Gy (2 fractions daily). For every patient, four treatment plans were prepared. Firstly, for five-lumen balloon optimized with IPSA algorithm and optimization parameters adjusted for each case. Secondly, for the same applicator optimized with dose point optimization and distant option. Two other plans were prepared for single-lumen applicator, created by removing four peripheral lumens, optimized with both algorithms. Results: The highest D95 parameter was obtained for plans optimized with IPSA algorithm, mean value 99.3 percent of prescribed dose, and it was significantly higher than plans optimized with dose point algorithm (mean = 83.50%, p < 0.0001), IPSA single-lumen balloon plan (mean = 83.50%, p = 0.0037) and optimized to dose point single-lumen balloon (mean = 85.51%, p < 0.0001). There were no statistically significant differences concerning maximum doses distributed to skin surface for neither application nor optimization method. Volumes receiving 200% of prescribed dose in PTV were higher for multi-lumen balloon dose point optimized plans (mean = 8.78%), than for other plans (IPSA multi-lumen balloon plan: mean = 7.37%, p < 0.0001, single-lumen IPSA: mean = 7.20%, p < 0.0001, single-lumen dose point: mean = 7.19%, p < 0.0001). Conclusions : Basing on performed survey, better dose distribution parameters are obtained for patients with multi-lumen balloon applied and optimized using IPSA algorithm with individualized optimization parameters.